2022-RA-1456-ESGO Ovarian cancer metastases in the liver area: a retrospective analysis of surgical, intraoperative and postoperative outcomes according to a standardize anatomo-surgical classification. (20th October 2022) - Rosati, Andrea; Pavone, Matteo; de Palma, Antonella; Conte, Carmine; Ghirardi, Valentina; de Rose, Agostino Maria; Giuliante, Felice; Scambia, Giovanni; Fagotti, Anna
Abstract : Introduction/Background: We recently developed an anatomo-surgical classification for ovarian cancer (OC) metastases in the liver area consisting in 5 different types (Type-1:Glisson's, Type-2:Ligamentous, Type-3:Gallbladder, Type-4:Hepatic hilum, Type-5:Liver parenchymal).This study aims to evaluate whether this classification is able to identify patients at greater risk of intra and postoperative complications and with increased surgical complexity. Methodology: All epithelial advanced-OC patients who underwent primary or secondary surgery with perihepatic liver involvement were retrospectively retrieved.Patients were classified according to our published anatomo-surgical classification and further clustered into four major Classes:Class-I or 'Peritoneal' (including Type1, 2, 3), Class-II or 'Hepatoceliac lymph-nodes'(Type-4), Class-III or 'Parenchymal'(Type-5) and Class IV or Mixed (≥2 classes). Results: 615 patients were identified, and Class I resulted as the most commonly represented (337 cases, 54.8%).The distribution of surgical complexity score (SCS) was superimposable among classes (p=0.239) while operative time and estimated blood loss were significantly longer/higher in Class IV (Mixed) (p<0.001). Intraoperative transfusions were more frequent in Class IV (30.4%) and less reported in Class-III (11.9%) (p=0.004); vascular injuries were significantly grouped in Class II (8%) (p=0.009).Class II and IV were more frequently associated to severe postoperative complications (p=0.008). Moreover, specific complications were found in each Class: perihepatic collection and intrahepatic hematoma/abscess in Class-III (respectively: p=0.003, p>0.001); pleuric effusion, sepsis, anemia and 'other complications' in Class IV (respectively: p=0.002, p=0.004, p=0.03, p=0.03).At Multivariate analysis SCS 3 and macroscopic residual tumor were identified as risk factors for severe postoperative complications (respectively: OR: 3.922, p=0.003 and OR: 1.748, p=0.048).Conversely, Class-I and III resulted to be at decreased risk for severe postoperative complications compared to Class IV. Conclusion: Our classification represents a useful and reliable tool, able to stratify patients with OC metastases in the liver area in Classes with different surgical outcomes and different postoperative complication profile.